Nephropathic cystinosis presenting with uveitis: Report of a "Can't See, Can't Pee" situation - Smita Mary Matthai; Shibu Jacob; Mandeep S Bindra; Vinoi George David; Santosh Varughese (Wolters Kluwer Medknow Publications, 2019)
Nephropathic cystinosis is a rare autosomal recessive lysosomal disease characterized by accumulation of pathognomonic cystine crystals in renal and other tissues of the body. Cystinosis is caused by mutant cystinosin, the cystine transport protein located in lysosomal membranes, leading to systemic deposits of cystine and resultant end organ damage. Cystinosis is rarer in Asians than Caucasians with only a handful of cases reported from India to date. Due to its extreme rarity and clinically insidious presentation in contrast to the infantile form, the diagnosis of juvenile nephropathic cystinosis is frequently delayed or overlooked. Moreover, routine processing and sectioning of paraffin embedded tissues dissolves cystine crystals, making it difficult to diagnose this condition on light microscopic examination alone, mandating electron microscopic (EM) analysis of renal biopsies for an accurate diagnosis of this condition. We describe a case of juvenile nephropathic cystinosis presenting with uveitis and photophobia in a 17-year-old Indian male, diagnosed after EM examination of the patient's renal biopsy for evaluation of nephrotic syndrome. While highlighting the diagnostic utility of EM, we describe a few histopathologic clues which can prompt inclusion of EM analysis of renal biopsies in this setting.